A87 ACTIVATION OF NR4A1 REDUCES INFLAMMATION-ASSOCIATED INTESTINAL FIBROSIS AND DAMPENS FIBROGENIC SIGNALING IN INTESTINAL MYOFIBROBLASTS. (15th March 2019) - Venu, V P; Alston, L; Szczepanski, H; Hirota, S A
Abstract: Background: Intestinal fibrosis is a common complication of IBD, comprises of excessive accumulation of scar tissue in the intestinal wall. Fibrosis is thought to result from an aberrant response to injury resulting in excessive extracellular matrix (ECM) deposition, which can lead to tissue stiffening and intestinal stricture formation. NR4A1 is an orphan nuclear receptor previously reported to regulate mesenchymal cell function and dampen fibrogenic signaling. More recently, NR4A1 gene variants were found to be associated with IBD risk, and its signaling shown to play a role in regulating intestinal inflammation. Aims: To test the hypothesis that NR4A1 acts as a negative regulator of intestinal fibrosis through regulating, myofibroblast function. Methods: Using the SAMP1-YitFc mouse, a spontaneous model of ileitis that exhibits extensive intestinal tissue remodelling, we administered NR4A1 agonists cytosporone B (CSN-B) or 6-mercaptopurine (6MP), beginning at 10 weeks of age (the age reported to be associated with established ileal inflammation in this model). Bodyweight and fecal lipocalin were assessed throughout the treatment period. After 12 weeks of NR4A1 agonist exposure, mice were sacrificed and intestinal tissues isolated for assessment of inflammatory markers and tissue ECM content. Histological analyses were performed to quantify tissue damage, inflammation, and remodelling. To determine the anti-proliferative effects of NR4A1, intestinal myofibroblast isolated from Nr4a1 +/+ and Nr4a1 -/- mice were exposed to TGF-β, treated with CSN-B or 6MP, and proliferation and ECM gene expression assessed. Results: SAMP1-YitFc treated with CSN-B or 6MP showed reduced body weight loss and a moderate reduction in inflammatory markers compared to the untreated mice. Ileal thickness and tissue collagen content was reduced in mice treated with CSN-B or 6MP. In vitro, Nr4a1 -/- intestinal myofibroblasts exhibited enhanced TGF-β-induced proliferation compared to Nr4a1 +/+ cells. Lastly, CSN-B and 6-MP each reduced TGF-β-induced proliferation in Nr4a1 +/+, but not Nr4a1 -/-, myofibroblasts. Conclusions: These data point towards targeting NR4A1 for the treatment of inflammation-associated fibrosis and suggest that 6MP, a commonly used agent for the treatment of IBD, may exhibit anti-fibrotic effects that should be reassessed in clinical studies. Funding Agencies: CIHR